Acute Lung Fibrosis Following Paraquat Poisoning - Das, Aparna; Neera, Naziha Sabah; Chowdhury, Forhad Uddin Hasan; Kahhar, Md Azizul (Bangladesh Journal of Medicine, 2018)
Paraquat is a potentially toxic herbicide that is used to eradicate common weeds. It is classified as a moderately hazardous (grade 2) pesticide by World Health Organization (WHO). Poisoning by paraquat carries significant mortality. It has an inclination to accumulate in lungs accelerating pulmonary fibrosis. We present a case report of a young man who accidentally ingested a mouthful of paraquat and subsequently developed fibrosis of lungs. Bangladesh J Medicine Jan 2018; 29(1) : 41-44